2019
DOI: 10.1111/jfpp.14235
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal effects of chitosan films incorporated with essential oils and control of fungal contamination in peanut kernels

Abstract: The study investigated the effects of chitosan (CS) combined with essential oils (EOs) in controlling the fungal contamination in peanut kernels. The antifungal activities of CS and EOs were evaluated against Aspergillus flavus and Penicillium citrinum. CS (2%, w/v in 1% v/v acetic acid) packaging films were formulated by incorporating different EOs (4%) separately, that is, thyme (TEOs), cinnamon (CEOs), and lemongrass (LEOs), respectively. CEOs showed lowest minimum inhibitory concentration (MIC) of 40 μl/ml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…BoŽik et al (2017) showed complete inhibition of A. flavus, A. parasiticus, and A. clavatus in oats by lemongrass, oregano, and thyme EOs. Chein et al (2019) investigated the efficacy of thyme, cinnamon, and lemongrass EOs to control the contamination of A. flavus and Penicillium citrinum at the lowest minimum inhibitory concentration of 40 µl/ml in peanuts kernels. Omidbeygi et al (2007) investigated the antifungal property of thyme and summer savory EOs against A. flavus in tomato paste at effective concentrations of 0.35 and 0.5 µg/ml, respectively.…”
Section: Application Of Essential Oils In Food System: Safety and Challengesmentioning
confidence: 99%
“…BoŽik et al (2017) showed complete inhibition of A. flavus, A. parasiticus, and A. clavatus in oats by lemongrass, oregano, and thyme EOs. Chein et al (2019) investigated the efficacy of thyme, cinnamon, and lemongrass EOs to control the contamination of A. flavus and Penicillium citrinum at the lowest minimum inhibitory concentration of 40 µl/ml in peanuts kernels. Omidbeygi et al (2007) investigated the antifungal property of thyme and summer savory EOs against A. flavus in tomato paste at effective concentrations of 0.35 and 0.5 µg/ml, respectively.…”
Section: Application Of Essential Oils In Food System: Safety and Challengesmentioning
confidence: 99%
“…Chitosan (CS), a linear cationic polysaccharide resulting from chitin deacetylation, is considered a suitable coating material due to its antimicrobial capacity and uniform lm-forming ability (Lai et al 2022). Chitosan exhibits antioxidant activity and broad-spectrum antibacterial activity against Salmonella, Lactobacillus, Listeria monocytogenes, and yeast (Chein et al 2019;Lin et al 2020; Molamohammadi et al 2019). In addition, several studies have reported that the combination of chitosan with other substances may show enhanced antibacterial and antioxidant effects compared to either single agent alone.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of EO, CS, and their combined mixture (EO + CS) on fungal hyphae were determined by following the method described by Chein et al 24 Potato dextrose broth (PDB, Himedia, India), 20 mL containing Tween 80 (2%, v/v) was inoculated with fungal spores (10 4 spores/ml) and placed in a shaking incubator (Wisecube, Seoul South Korea) at 30 °C and 180 rpm. After 48 h, hyphae were harvested by centrifugation (DLAB D3024R, China) at 4,500× g for 5 min, and were then washed (twice) with phosphate buffer saline (PBS, pH 7.4).…”
Section: Effect Of Eo and Cs On Fungal Hyphaementioning
confidence: 99%
“…The reported variations in MIC values of EO might be due to the variations in composition of EO due to different extractions methods, cultivation season, different test strains of fungi. 24,34 FTIR analysis Functional groups of EOs from fresh and dried peels of sweet orange were identified by FTIR (Fig. 2 and supplementary material, Table S1).…”
Section: Radial Growth Inhibition Assay (Rgi)mentioning
confidence: 99%
See 1 more Smart Citation